Use of Sunkist Orange Fruit (Citrus sinensis) Juice In Mozzarella Cheese Manufacturing - Djalal Rosyidi; Purwadi Purwadi; Fondha Teguh Eko Harjono (Faculty of Animal Science Universitas Brawijaya, 2007)
Data collecting of this research was administered since February until March 2006 in the Animal Product Technology Laboratory of Animal Husbandry Faculty Brawijaya University Malang, Biological Laboratory of Muhammadiyah University Malang and Engineering Laboratory Centre Food and Laboratory Â Gadjah Mada University Yogyakarta. The objective of this research was to know the best concentration of Sunkist orange fruit juice with direct acidification in Mozzarella cheese manufactured considered on yield, protein content, moisture content, stretchability and meltability. Hopefully the result would support in producing cheese earlier and better quality processed with direct acidification from Sunkist orange fruit juice. Method of this research was experiment used Completely Randomized Design and repeats four times. The treatment was Sunkist orange fruit juice concentration of 3% (P1), 3.5% (P2), 4% (P3) and 4.5% (P4) from milk volume. Variables measured would be yield, protein content, moisture content, stretchability and meltability. The data were analyzed by analysis of variance andÂ Duncans Multiple Range Test. The result showed that Sunkist orange fruit juice did not give significant different effect (P>0.05) on yield, stretchability and meltability, in the otherwise give highly significant different effect (P<0.01) on protein and moisture content of Mozzarella cheese. The conclusion of this research was the Sunkist orange fruit juice concentration of 3% was the best concentration and suggested to use on Mozzarella cheese manufacturing. Â Keyword : Mozzarella cheese, orange fruit.